IRANIAN WOMEN'S RIGHTS ACTIVISTS AND THEIR UNDERSTANDING OF CORE CONCEPTS OF CRITICAL MEDIA LITERACY - Kobra Mohammadpour KACHLAMI (Social Sciences and Education Research Review)
Media has an important role in socializing Iranian women into sexism and patriarchy. The women have been indoctrinated to believe that gender inequality is natural and neutral, so they do not challenge the existing power structure. Given the power of media in shaping Iranian women's identity, it is imperative to be analyzed critically. The current study investigates how Iranian women's rights activists understand the core concepts of critical media literacy. Through a qualitative approach and conducting semi-structured interviews with 15 Iranian women's rights activists, this study reveals that the activists know the five core concepts, non-transparency, audience interpretation, politics of representation, media motivations, and social justice. However, they know little about other core concepts, languages and techniques, and how the media could subordinate women further through employing these techniques.